PLD realization of the two-rail code addition device - Пащенко, Н. В. (Problems of Informatization and Control, 2009)
The problem of the data control in computer systems is considered. The opportunity of application of the control schemes based on code "M out of N" is investigated to increase productivity and data reliability level. Hardware realization of the two-rail code addition device is offered